Dificuldades e limitações das luvas de proteção usadas no corte manual da cana - Maria Cristina Gonzaga; Cristiane Queiroz Barbeiro Lima (Universidade do Porto, 2016)
he present study is based on previous researches into the use of safety gloves in manual sugarcane harvesting. It analyses the certification and approval process of this PPE, discussing the issue of the distance between the test standards for the production of protective equipment for the users and the actual activity to be performed. It highlights the importance of the recognition of the various sizes of hands to the selection of safety gloves, as well as it stresses the number of accidents and occupational diseases registered in the activity involving hands, justifying the relevance of their use. During the study, it was observed how the main work tool - the cutting blade - is readapted by the workers to be used with efficiency in the productive process. It presents suggestions made by the workers in order to improve the gloves and the cutting blade. At last, it points out the challenges of recognising and discussing the difficulties and limitations of the use of PPE and of its certification system.